Social preferences during childhood and the role of gender and age: An experiment in Austria and Sweden - Peter Martinsson; Katarina Nordblom; Daniela Rützler; Matthias Sutter (University of Innsbruck, Department of Public Finance, 2010)
We examine social preferences of Swedish and Austrian children and adolescents using the experimental design of Charness and Rabin (2002). We find that difference aversion decreases while social-welfare preferences increase with age.
Keywords: C91; D63; D64; 330; social preferences; children; adolescents; distributional experiment; Austria; Sweden.; Entscheidung; Soziale Werte; Soziales Verhalten; Geschlecht; Altersgruppe; Test; Kinder; Jugendliche; Österreich; Schweden